EFFORTS TO IMPROVE THE ABILITY TO USE MEASURING INSTRUMENT STUDENT LEARNING THROUGH MEDIA MACROMEDIA FLASH IN CLASS X MECHANICAL MACHINING SMK 1 SEDAYU ACADEMIC YEAR 2012/2013 - Puput Hananto; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2013)
This study aimed to describe the effect of instructional media makromedia flash in improving the students practical skill on subjects Measure Measuring Precision Mechanics class X Mechanical Engineering SMK 1 Sedayu Academic Year 2012/2013.This study included in Classroom Action Research (CAR). This study was conducted in two cycles, in 1 cycle has 3 times with the research subjects are class X students of SMK 1 Sedayu TPm totaling 32 students. The data were obtained from observations during learning activities by using observation sheets, tests, documents and photographs. Results obtained were analyzed with descriptive statistical analysis.The results showed that the ability of the students to practice using instructional media on subjects macromedia flash Measuring with Precision Mechanical Measuring Instrument has increased as follows: the initial capabilities obtained an average value of 65.9 after treatment in the first cycle the average value becomes 76.1. While the values obtained in the second cycle to 84.8 average. Based on the study results, the authors suggest that teachers improve the application of instructional media in learning macromedia flash so the ability to practice and student achievement will increase.